2021
DOI: 10.1111/ajt.16349
|View full text |Cite
|
Sign up to set email alerts
|

Liver transplantation in a patient after COVID-19 – Rapid loss of antibodies and prolonged viral RNA shedding

Abstract: To date, little is known about the duration and effectiveness of immunity as well as possible adverse late effects after an infection with SARS‐CoV‐2. Thus it is unclear, when and if liver transplantation can be safely offered to patients who suffered from COVID‐19. Here, we report on a successful liver transplantation shortly after convalescence from COVID‐19 with subsequent partial seroreversion as well as recurrence and prolonged shedding of viral RNA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 11 publications
0
31
0
Order By: Relevance
“…Prolonged SARS-CoV-2 RNA shedding has been mostly reported in immunocompromised patients (7)(8)(9)(10). These studies demonstrated that a decline or delay in antibody response could lead to relapse or recovery of COVID-19 (7). However, in a recent report involving a lymphoma patient with low immunity response, the patients were re-tested as positive for SARS-CoV-2 RNA after administration of COVID-19 convalescent plasma transfusion (11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prolonged SARS-CoV-2 RNA shedding has been mostly reported in immunocompromised patients (7)(8)(9)(10). These studies demonstrated that a decline or delay in antibody response could lead to relapse or recovery of COVID-19 (7). However, in a recent report involving a lymphoma patient with low immunity response, the patients were re-tested as positive for SARS-CoV-2 RNA after administration of COVID-19 convalescent plasma transfusion (11).…”
Section: Introductionmentioning
confidence: 99%
“…Prolonged SARS-CoV-2 RNA shedding has been mostly reported in immunocompromised patients ( 7 10 ). These studies demonstrated that a decline or delay in antibody response could lead to relapse or recovery of COVID-19 ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Early in the pandemic, there were only a handful of case reports describing patients who successfully underwent DDLT after recovery from SARS-CoV-2 infection. [51][52][53] In these reports, all patients had recovered with negative polymerase chain reaction (PCR) tests prior to transplantation, with the earliest transplant occurring 36 days after onset of symptoms. In one case where the patient's induction immunosuppression regimen consisted of only steroids and a calcineurin inhibitor, the patient experienced acute rejection requiring thymoglobulin and high dose steroids, without any adverse events thereafter.…”
Section: Accepted Articlementioning
confidence: 99%
“…[8][9][10] In cases of transplantation soon after COVID-19 recovery, the viral polymerase chain reaction (PCR) was negative on more than one test for all patients prior to transplant. [11][12][13][14] Only one case exists of transplantation with a positive PCR. However, in this lung transplant recipient's preoperative swabs, the cycle threshold-the number of amplification cycles needed to detect genetic material of the virus-was persistently high, and virus was not cultured.…”
Section: Lack Of Data To Support Transplanting Actively Infected Patientsmentioning
confidence: 99%